A coordinated optimization model for analysis of electric vehicle acceptance capacity considering compensation units - Chen, Sheng; Zhang, Honglue; Chen, Zhiqi; Li, Shousong; Fu, Tongfu; Sui, Yunyun (Frontiers in Energy Research, 2025)
IntroductionPromoting the adoption of Electric Vehicles (EVs) is widely recognized as an effective strategy for addressing environmental challenges. Consequently, the expansion of EV charging infrastructure is necessary to enhance the user experience and accommodate the increasing demand. However, without careful consideration of optimal site selection and capacity planning, the integration of EV charging loads may induce significant overcapacity and voltage fluctuating issues.MethodsThis paper presents a coordinated optimization model for assessing the integration acceptance capacity of EV charging loads within distribution networks. The model is based on linear power flow equations and incorporates the compensatory capabilities of the distribution network.Results and discussionA case study is conducted to evaluate the acceptance capacity of two distinct types of EV charging loads within the IEEE 33-bus benchmark network. Additionally, the paper examines the impact of various system expansion strategies on the acceptance capacity, considering the aggregation of different units. The results indicate that energy storage systems (ESSs) and static var generators (SVGs) exert the most significant influence on the network’s ability to accommodate EV charging loads.